The generalized De Rham-Hodge theory of Delsarte transmutation operators in multidimension case and its applications - Prykarpatsky, Y.A.; Samoilenko, A.M. (Нелінійні коливання, 2004)
A study of spectral and differential-geometric properties of Delsarte transmutation operators is given. Their
differential geometrical and topological structure in multidimension is analyzed, the relationships with the
generalized De Rham – Hodge theory of generalized differential complexes are stated. Some applications
to integrable dynamical systems in multidimension are presented. Вивчено спектральнi та диференцiально-геометричнi властивостi трансмутацiйних операторiв Дельсарта. Проведено аналiз їх диференцiально-геометричної та топологiчної структур у
багатовимiрному випадку. Встановлено зв’язок з узагальненою теорiєю Де Рама – Ходжа узагальнених диференцiальних комплексiв. Наведено деякi застосування до теорiї iнтегровних динамiчних систем у багатовимiрному випадку.